Predicting The Risk Of Cardiovascular Complications In Patients With Psoriatic Arthritis - Abdullaev U.S (Genius Journals, 2024)
According to modern researchers, one of the most common comorbid diseases in patients with psoriatic arthritis (PsA) is cardiovascular pathology (CVP). The trend frequency of cardiovascular pathology (CVP) has a high probability of developing cardiovascular complications (CVC), which leads to early disability in PsA patients. This is the reason for in-depth analysis of risk factors and predicting the risk of cardiovascular complications (CVC) in PsA patients.
Keywords: Psoriatic arthritis; cardiovascular complications; cardiovascular pathology